2021
DOI: 10.1371/journal.pone.0251791
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprevotella muciniphila gen. nov., sp. nov., a mucin-degrading bacterium attached to the bovine rumen epithelium

Abstract: A Gram-negative, strictly anaerobic mucin-degrading bacterium, which we designated strain E39T, was isolated from the rumen epithelium of Korean cattle. The cells were non-motile and had a coccus morphology. Growth of strain E39T was observed at 30–45°C (optimum, 39°C), pH 6.5–8.5 (optimum, pH 7.5), and in the presence of 0.0–1.0% (w/v) NaCl (optimum, 0.0–0.5%). Strain E39T contained C16:0, C18:0, C18:1 ω9c, iso-C15:0, and anteiso-C15:0 as the major fatty acids. The major polar lipids were phosphatidylethanola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Also, culture-dependent studies are needed to understand rumen epithelial host-microbe interactions. To date, only a few recent studies have identified novel rumen bacteria from the rumen epithelium ( Hong et al., 2020 ; Na et al., 2021 ), and continuous efforts to isolate novel epimural microbes are essential for epimural microbiome study.…”
Section: Future Directions To Study Epithelial Host-microbe Interacti...mentioning
confidence: 99%
“…Also, culture-dependent studies are needed to understand rumen epithelial host-microbe interactions. To date, only a few recent studies have identified novel rumen bacteria from the rumen epithelium ( Hong et al., 2020 ; Na et al., 2021 ), and continuous efforts to isolate novel epimural microbes are essential for epimural microbiome study.…”
Section: Future Directions To Study Epithelial Host-microbe Interacti...mentioning
confidence: 99%